Integrating Metacognition into Adaptive Gamification Design to Strengthen Reflective Competence in Pre-service Teacher Education - Kawatu, Paul Johan; Dewanti, Lucky; Astuty, Henny Sri; Sodikin, Sodikin; Arafah, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2025)
Reflective competence is vital for prospective teachers to foster critical thinking and lifelong learning. However, digital learning environments often lack support for metacognitive awareness and self-regulation. This study used a quasi-experimental mixed-methods design involving 128 education students from two Indonesian LPTKs over one semester. Pre-tests and post-tests using the Reflective Thinking Scale (RTS) assessed quantitative changes, while qualitative data came from learning logs and interviews. Results showed a significant improvement in reflective competence (p < 0.01), particularly in critical reflection and thinking strategies. Adaptive gamification that adjusted challenges and feedback in real time enhanced engagement and learning depth. Metacognitive integration in gamification promoted self-regulation, reflective questioning, and skill transfer to teaching practice. Metacognition-based adaptive gamification effectively supports the development of reflective competence in prospective teachers.